Facts and values in psychotherapy—A critique of the empirical reduction of psychotherapy within evidence‐based practice - Berg, Henrik; Slaattelid, Rasmus (Journal of evaluation in clinical practice, 2017)
This paper addresses an implicit presupposition in research‐supported psychological treatments and evidence‐based practice in psychology. It argues that the notion of research‐supported psychological treatments is based on a reductive conceptualisation of psychotherapy. Research‐supported psychological treatments hinge upon an empirical reduction where psychotherapy schools become conceptualized as mere collections of empirical propositions. However, this paper argues that the different psychotherapy schools have distinct ethoses that are constituted by normative claims. Consequently, the evaluation of the different psychotherapy schools and the practice of psychotherapy should include the underlying normative claims of these ethoses.